Case Report: Stent Retriever Thrombectomy of Acute Basilar Artery Occlusion via the Type 1 Proatlantal Intersegmental Artery - Zhao, Lei; Yang, Lijun; Liu, Xiaosong; Wang, Xiaoliang; Zhang, Gengshen; Wu, Jianliang (Frontiers in Neurology, 2022)
Stent retriever thrombectomy (SRT) is one of the most effective methods for the recanalization of acute basilar artery occlusion (ABAO). The proatlantal intersegmental artery (PIA) is a rare carotid-vertebrobasilar anastomosis. Recognition of this rare form of anastomosis is particularly important for the rapid establishment of positive blood flow in patients with ABAO. In this case, the patient had a rare, left type 1 PIA. The right vertebral artery (VA) was tenuous and did not enter the cranium. We performed a thrombectomy of the ABAO by inserting a catheter via the type 1 PIA. The complete recanalization of basilar artery (BA) flow was achieved following two stent retractions; however, the patient eventually died of brain stem hemorrhage.